Perbandingan Algoritma Flyoid Warshal Dan Djikstra Menentukan Jarak Terdekat Aplikasi Pencarian Pemesanan Rumah Sewa Berbasis Mobile - Ananda Faridhatul Ulva; Mochamad Ari Saptari; M Taufiq Hariadi (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2022)
A rental house is a type of rental that is rented out (contracted) for a certain period of time at a price agreed upon by the owner of the room. Lhokseumawe City as a district that has several State Universities and the presence of large companies, such as Perta Arun Gas and PIM made many other residents from other cities look for a place to live in Lhokseumawe City. The difficulty and lack of information about a rental house for new residents makes it difficult for them to find a rental house that is comfortable for them, some are even far from where they are studying. The difficulty of newcomers in getting information about rental houses in Lhokseumawe City provides an overview by researchers to research a system for searching for rental houses in Lhokseumawe City based on mobile. The system development method to build this application uses the SLDC principle, namely the waterfall, where this method uses the concept of a waterfall, performs sequential development that is dynamic and structured in building a software, with a system requirements analysis process, system design, coding, testing, and implementation. Based on the trials that have been carried out, using the Floid Warshall and Djikstra algorithms in determining the shortest route to the rental house, Flyod Warshall is the most optimal search algorithm in the results of determining the shortest distance, with the smallest optimal number of distances compared to Djikstra. It is hoped that in the future this application can be updated with the concept of other shortest distance comparison methods, so as to get more optimal results in implementing the system.